POSITIVE POLITENESS STRATEGIES EMPLOYED BY THE CHARACTERS IN TURNING RED MOVIE - Laila Marfirah; Ambalegin, Ambalegin (eScience Humanity Journal, 2023)
This research was purposed to discover the positive politeness strategy by using the  theory from Brown and Levinson (1987). And for the data source, this research took a movie “Turning Red”. This study used the descriptive qualitative method from Creswell (2013). In collecting and analyzing the data this research applied the theory from Sudaryanto (2015). It was found 21 data of positive politeness done by the characters. The strategy 10: Offer, promise occurred 5 times was most strategy used. Strategy 2: Exaggerate occurred 2 times. Strategy 4: Use in-group identity markers appeared 2 times. Strategy 5: Seek agreement appeared 1 time. Strategy 7: Presuppose appeared 1 time. Strategy 9: Assert or presuppose speaker knowledge of and concern for hearer wants appeared 2 times. Strategy 12: Include both speaker and hearer in the activity was 4 times occurrence. Strategy 14: Assume or assert reciprocity occurred 3 times. And Strategy 15: Give gift occurred 1 time.